Determinants of changes in harvested area and yields of major crops in China - Yin, Fang; Sun, Zhanli; You, Liangzhi; Müller, Daniel (Springer, 2024)
Global agricultural production has risen substantially in recent decades and needs to rise further to meet the ever-growing food demand. While higher production can be directly attributed to agricultural expansion and intensification, the underlying factors behind the changes in cultivated areas and yields can be complicated and have not been well understood. China has dramatically increased its food production in past decades, especially during the initial approximately 30 years following the commencement of the rural reform in the late 1970s. The agricultural land use, including cropland areas, the composition of different crops and their spatial distributions, and crop yields have experienced substantial changes. In this research, we quantitatively analysed the changes in the harvested areas and yields of the four most widely cultivated crops in China (rice, wheat, maize, and soybean) at the county level from 1980 to 2011. We used spatial panel regressions to quantify the determinants of the observed changes in harvested area and yields for the major cultivation region of each of the four crops. Results showed that growth in population, gross domestic product, and urbanisation are positively associated with harvested areas. Higher usage of machinery and fertiliser inputs increased yields of the three cereal crops, while the harvested area of soybean decreased, particularly after China’s accession to the WTO. Our findings reveal how domestic urbanisation and changes in consumption patterns, coupled with the rising globalisation of agricultural markets, shaped China’s agricultural production and land use over the three decades. These insights shed light on the determinants of long-term agricultural dynamics and thus inform evidence-based decision-making.